2017
DOI: 10.1080/17435390.2017.1378749
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility assessment of functionalized magnetic mesoporous silica nanoparticles in human HepaRG cells

Abstract: Magnetic mesoporous silica nanoparticles (M-MSNs) are a promising class of nanoparticles for drug delivery. However, a deep understanding of the toxicological mechanisms of action of these nanocarriers is essential, especially in the liver. The potential toxicity on HepaRG cells of pristine, pegylated (PEG), and lipid (DMPC) M-MSNs were compared. Based on MTT assay and real-time cell impedance, none of these NPs presented an extensive toxicity on hepatic cells. However, we observed by transmission electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…The lack of a toxic effect of PEG-coated mesoporous silica nanoparticles was already reported for this hepatic cell line [33]. While CdTe quantum dots alone present toxicity on HepG2 cells [34] after 6, 12, and 24 h incubations, at concentrations up to 1 μg/mL in Cd 2+ (with mitochondrial swelling and mitochondrial membrane disruption, increase in Ca 2+ intracellular levels, decrease in cellular respiration and depression of ATP levels), the silica coating of these CdTe quantum dots is expected to reduce this toxicity [35].…”
Section: Resultsmentioning
confidence: 78%
“…The lack of a toxic effect of PEG-coated mesoporous silica nanoparticles was already reported for this hepatic cell line [33]. While CdTe quantum dots alone present toxicity on HepG2 cells [34] after 6, 12, and 24 h incubations, at concentrations up to 1 μg/mL in Cd 2+ (with mitochondrial swelling and mitochondrial membrane disruption, increase in Ca 2+ intracellular levels, decrease in cellular respiration and depression of ATP levels), the silica coating of these CdTe quantum dots is expected to reduce this toxicity [35].…”
Section: Resultsmentioning
confidence: 78%
“…The use of silica coatings has revealed an improvement in the chemical stability of the magnetic nanoparticles and reduction of their toxicity, so conjugation of mesoporous silica nanoparticles with magnetic nanoparticles has been arousing great interest in nanomedicine as targeting tools for theranostics [ 3 ]. Their combined properties allow the co-delivery of therapeutic and imaging functions with the convenience of magnetically guided delivery (magnetofection), as the systems can be led to target sites by controlling the external magnetic field (EMF), increasing the therapeutic efficiency and minimizing the non-specific distribution [ 114 , 115 , 116 ].…”
Section: Hybrid Silica Nanoparticlesmentioning
confidence: 99%
“…Pristine, PEGylated, and lipid (DMPC)-coated magnetic MSNs were evaluated, and neither were extremely harmful to liver cells, having the authors set a limit of biocompatibility of 60 μg/mL of these NPs for these cells. The maximum decrease in cell viability corresponded to 35% and was reached by 48 h of exposure to 400 μg/mL of pristine NPs, which also demonstrated the improvement in biocompatibility achieved with the surface modifications [ 114 ].…”
Section: Biocompatibility Of Silica-based Materialsmentioning
confidence: 99%
“…In the drug release study, a sustained release behavior was observed with about 60% of loaded HAS2 (MSN-CC-PEI + HAS2) released in 12 h ( Figure S1F, Supporting Information). [28] Even the good biocompatibility of MSNs toward animal cells and/or cancer cell lines is widely reported, [29,30] their toxicity on human primary cells is rarely reported. [24] As shown in Figure S15 in the Supporting Information, 89% enzymatic activity of β-Gal was retained after loaded into MSN-CC-PEI.…”
Section: Doi: 101002/adma201904535mentioning
confidence: 99%